Antibiotics as Anti-Inflammatory and Immunomodulatory Agents - Bruce K. Rubin , Jun Tamaoki (2005)
This book is divided into two sections; the first, on basic research, evaluates the effects of macrolide antibiotics on bacteria other than by ribosomally-mediated bacteriostasis. Specifically the macrolide antibiotics have been shown to influence the expression of virulence factors in gram-negative organisms and decrease the ability of these bacteria to form biofilms as detailed in the chapters by Kazuhiro Tateda, Theodore J Standiford, and Keizo Yamaguchi. A series of six chapters then follow detailing the various anti-inflammatory and immunomodulary effects of these antibiotics. Immunomodulation in this sense refers to the ability to downregulate deleterious hyperimmunity leading to airway damage as opposed to anti-inflammatory properties, which refers to the suppression of all inflammatory responses whether beneficial or not. Thus immunomodulation should not impair the normal host defense but will prevent an acute inflammatory response from becoming chronic and destructive inflammation. Michael Parnham gives a superb overview of the role of inflammation and its resolution with antibiotics. This is then followed by chapters that document the effect of macrolide antibiotics on cell membrane protection and epithelial stabilization (Charles Feldman and Ronald Anderson), neutrophil activation and chemotaxis (Jun-ichi Kadota), reduction of proinflammatory cytokine expression and release (HajimeTakizawa), the oxidative burst (MarieThérèse Labro), and immune activation (Jun-ichi Kadota).